Impact of intense sanitization on environmental biofilm communities and the survival of Salmonella enterica at a beef processing plant - Wang, Rong; Guragain, Manita; Chitlapilly Dass, Sapna; Palanisamy, Vignesh; Bosilevac, Joseph M. (Frontiers in Microbiology, 2024)
Salmonella enterica is a leading cause of foodborne illness in the U.S. In the meat industry, one action taken to address pathogen contamination incidence is an intense sanitization (IS) of the entire processing plant that many large processors perform annually or semiannually. However, this procedure's immediate and long-term impact on environment microbial community and pathogen colonization are unknown. Here we investigated the impact of IS procedure on environmental biofilms and the subsequent S. enterica colonization and stress tolerance. Environmental samples were collected from floor drains at various areas 1 week before, 1 week, and 4 weeks after the IS procedure at a beef plant with sporadic S. enterica prevalence. Biofilm formation by microorganisms in the drain samples without S. enterica presence was tested under processing temperature. The ability of the biofilms to recruit and/or protect a co-inoculated S. enterica strain from quaternary ammonium compound (QAC) treatment was determined. The community structure of each drain sample was elucidated through 16S rRNA amplicon community sequencing. Post-IS samples collected from 8 drains formed significantly stronger biofilms than the respective pre-IS samples. S. enterica colonization was not different between the pre- and post-IS biofilms at all drain locations. S. enterica survival in QAC-treated pre- and post-IS mixed biofilms varied depending upon the drain location but a higher survival was associated with a stronger biofilm matrix. The 16S rRNA amplicon gene community sequencing results exhibited a decrease in community diversity 1 week after IS treatment but followed by a significant increase 4 weeks after the treatment. The IS procedure also significantly altered the community composition and the higher presence of certain species in the post-IS community may be associated with the stronger mixed biofilm formation and Salmonella tolerance. Our study suggested that the IS procedure might disrupt the existing environmental microbial community and alter the natural population composition, which might lead to unintended consequences as a result of a lack of competition within the multispecies mixture. The survival and recruitment of species with high colonizing capability to the post-IS community may play crucial roles in shaping the ensuing ecological dynamics.